Understanding the Aerodynamic Behavior and Energy Conversion Capability of Small Darrieus Vertical Axis Wind Turbines in Turbulent Flows - Francesco Balduzzi; Marco Zini; Andreu Carbó Molina; Gianni Bartoli; Tim De Troyer; Mark C. Runacres; Giovanni Ferrara; Alessandro Bianchini (Energies, 2020)
Small Darrieus vertical-axis wind turbines (VAWTs) have recently been proposed as a possible solution for adoption in the built environment as their performance degrades less in complex and highly-turbulent flows. Some recent analyses have even shown an increase of the power coefficient for the large turbulence intensities and length scales typical of such environments. Starting from these insights, this study presents a combined numerical and experimental analysis aimed at assessing the physical phenomena that take place during the operation of a Darrieus VAWT in turbulent flows. Wind tunnel experiments provided a quantification of the performance variation of a two-blade VAWT rotor for different levels of turbulence intensity and length scale. Furthermore, detailed experiments on an individual airfoil provided an estimation of the aerodynamics at high turbulence levels and low Reynolds numbers. Computational fluid dynamics (CFD) simulations were used to extend the experimental results and to quantify the variation in the energy content of turbulent wind. Finally, the numerical and experimental inputs were synthetized into an engineering simulation tool, which can nicely predict the performance of a VAWT rotor under turbulent conditions.